Family structures and restructures in Romanian society. Parental alienation syndrome - Matei Raluca Silvia; Enache Rodica Gabriela (Technium Social Sciences Journal, 2021)
In this paper we describe some problems of the Romanian families in contemporary society: marital satisfaction, psychological and social implications of divorce and parental conflicts and the parental alienation syndrome